Pain Management in Hypertension Through Pressure Point Massage - Widayati, Dhina; Rachmania, Diana (Chakra Brahmanda Lentera Institute, 2024)
Background: Hypertension is a disorder of the cardiovascular system characterized by increased blood pressure that causes pain in the back of the neck area. Giving a massage is one effort to reduce pain. This study was to determine the effect of pressure point massage on pain levels in hypertension. Methods: The design of this research was pre-experiment, involving 44 respondents by purposive sampling from 73 people with hypertension as a population. The dependent variable of pain level was measured using a pain scale, and the data was analyzed by paired t-test with α 0.05 Results: The results were a decrease in pain levels (pre-test 77.3% moderate pain and post-test 87% mild pain). The results of the data analysis using paired t-test were obtained p-value = 0.001 (<α), showing that there was an influence of pressure point massage on the level of pain in hypertension. Conclusion: Blood circulation becomes smooth because of pressure point massage, which can stimulate endorphin neurotransmitters in the autonomic nerves so that the body relaxes. Pressure point massage intervention can be applied as an alternative therapy option in the management of hypertension, which supports the treatment of hypertension so that blood pressure can be well controlled.